Simulation Studies of Quail Hunting Success Associated with Ecological Succession of Planted Pine Stands - John D. Gavitt; Robert H. Giles Jr. (National Quail Symposium Proceedings, 2017)
A concept paper of a methodology is presented for explaining past populations and predicting future populations of bobwhite quail (Colinus virginianus), as a function of forest changes. The methodology is applicable to large landholdings, regions, and states. It relates, using computer technology, the number of potential covey flushes per 100 acres per day to the age of forest stands or ecological succession curves. By summing quail flush curves over a large area, area-wide yields may be obtained. Flushes are modified by a shooting-quality factor and birds per covey. The computer-generated output tables provide an inventory, a historical overview, and projected populations. The results are useful for making forestry-wildlife tradeoffs, for explaining quail declines or increases as a result of forestry operations, and for improvements in allocating money to wildlife or forestry. The method is based on a similar system for big-game forage in the Pacific Northwest (2) and is now being developed.